2018
DOI: 10.33086/jhs.v10i2.140
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Self Efficacy Dengan Perilaku Self Care Pasien Pasca Stroke Di Rumah Sakit Islam Surabaya

Abstract: The post-stroke can be regarded as the most difficult time for patients with post-stroke, they will experience a disability and inability to move as usual so that they will have difficulty in self care. The research was purposed to analyze the relationship of self-efficacy with self-care behavior of patients with post-stroke Islamic Hospital A Yani Surabaya. This study design was analytic correlation with cross sectional approach. The population of 36 people and a large sample of 36 respondents using purposive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
2
5
0
11
Order By: Relevance
“…3) change negative emotions. 4) Correct misinterpretation of the state of the body Wantiyah theory ( 2010) along with the development of adulthood, the increasing number of stressor level problems can affect an individual's self-efficacy (Ismatika & Soleha, 2018). At the TMS clinic of RSUD Dr. R Koesma of Tuban, we found that most of the high self-efficacy was found in patients with middle adulthood and early adulthood.…”
Section: Discussionmentioning
confidence: 79%
“…3) change negative emotions. 4) Correct misinterpretation of the state of the body Wantiyah theory ( 2010) along with the development of adulthood, the increasing number of stressor level problems can affect an individual's self-efficacy (Ismatika & Soleha, 2018). At the TMS clinic of RSUD Dr. R Koesma of Tuban, we found that most of the high self-efficacy was found in patients with middle adulthood and early adulthood.…”
Section: Discussionmentioning
confidence: 79%
“…Keyakinan diri terhadap kemampuan untuk melakukan self care merupakan penting disetiap tahap self care untuk mencapai keberhasilan (Ismatika & Soleha, 2017). Self-efficacy menjadi salah satu faktor dalam peningkatan kualitas hidup pasien yang menderita penyakit kronik menahun khususnya yang memiliki proses pengobatan lama seperti kanker, tuberkulosis, diabetes millitus dan penyakit jantung (Afandi & Kurniawan, 2018;Kurniawan et al, 2019;Omran & Mcmillan, 2018).…”
Section: Pembahasanunclassified
“…Pada aktivitas mencapai kesuksesan dalam menyelesaikan suatu masalah, individu tersebut dapat meningkatkan self efficacy yang mampu mempertahankan dan meningkatkan kesehatannya. (Ismatika and Soleha, 2018).…”
Section: Analisis Faktor Demografi Umur Dengan Self Efficacyunclassified